2017
DOI: 10.5937/inovacije1702141s
|View full text |Cite
|
Sign up to set email alerts
|

English language teachers' attitudes towards inclusive education

Abstract: The paper studies attitudes of teachers of English as a foreign language (EFL) towards inclusion of children with special educational needs (SEN) in Serbian mainstream schools. The participants were 96 primary teachers of English with diverse experience in teaching inclusive EFL classes. The results showed that most of the respondents (N=84. i.e. 87.5%) had negative attitudes towards inclusion, due to both the lack of competences and to the absence of adequate conditions for effective inclusive practice: only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Their inaction can cause indifference and demotivation among the teaching staff (García et al, 2016) and this cannot be afforded by SEN students. As an example, Savic and Prosic‐Santovac (2017) revealed that 87.5% of the EFL teachers polled in their research showed negative attitudes toward inclusion due to the absence of adequate conditions for effective inclusive practice. Hence, to change negative for positive attitudes, authorities should improve the conditions in our schools (Savic & Prosic‐Santovac, 2017), make the allocation of the available resources more flexible (based on the severity of needs represented in the inclusive settings) and set learning support teams within the schools to care for individual teachers who request guidance over a teaching concern related to SEN (Avramidis & Norwich, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Their inaction can cause indifference and demotivation among the teaching staff (García et al, 2016) and this cannot be afforded by SEN students. As an example, Savic and Prosic‐Santovac (2017) revealed that 87.5% of the EFL teachers polled in their research showed negative attitudes toward inclusion due to the absence of adequate conditions for effective inclusive practice. Hence, to change negative for positive attitudes, authorities should improve the conditions in our schools (Savic & Prosic‐Santovac, 2017), make the allocation of the available resources more flexible (based on the severity of needs represented in the inclusive settings) and set learning support teams within the schools to care for individual teachers who request guidance over a teaching concern related to SEN (Avramidis & Norwich, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, collaboration can be improved most of the time (Colmenero Ruiz & Pegalajar Palomino, 2015; Schwab et al, 2019). Savic and Prosic‐Santovac (2017) reported that almost 70% of respondents in their study carried out in Serbia admitted that SEN teams rarely met, and in Spain, Reoyo et al (2012) and Hernández and Carrasco (2012) showed that preservice secondary teachers think that the lack of coordination and communication perceived during their practicum makes total inclusion hard to achieve.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations